Thought News: A Quest For Democratic Communication Technology - Pinter, Andrej (Javnost-The Public, 2003)
This paper presents an analytical framework for a reading of the Thought News project as an attempt to democratize the means of mass communication. The project was a creative endeavour of a former journalist Ford, and the American pragmatists, Dewey, Park, and Mead to set up an accessible newspaper about complex social processes. Because of its emphasis on the conditions of information diffusion as integrative and on the possible social bearing of theoretical knowledge, the project represents a typical nineteenth century reflection on mass communication. In this sense, it is comparable to the contemporaneous theories of Tarde and Schäffle, who similarly sought to improve the performance of the press. Arguably, central concerns of the project have not been obliterated by the new communication technologies, but persist instructively for our present uses of them.